The antiplatelet and anticoagulant activity of 7-O-gentiobiozide formononetin in vitro and in vivo - Ya. F. Zverev; A. V. Kudinov; A. P. Momot; S. A. Fedoreyev; S. V. Zamyatina; N. I. Kulesh; N. A. Lychova; D. V. Fyodorov (Бюллетень сибирской медицины)
Aim. In experiments in vitro and in vivo it was investigated the effect of isoflavone 7-O-gentiobiozide formononetin (GBF) isolated from the roots of the plant Maackia аmurensis (Maackia amurensis Rupr. et Maxim.), on the processes of vascular-platelet and coagulation hemostasis.Materials and methods. In experiments using blood of healthy human plasma in concentrations of GBF 1,0–50,0 mM promoted dose-dependently ADP-induced weakening of platelet aggregation. Since the concentration of 10,0 mM GBF induced hypocoagulative changes in blood plasma, comparable with the effect of 0,2–0,5 IU/ml heparin. Revealed hypocoagulative effect was confirmed in the application thromboelastometry, showing pronounced hypocoagulation and a significant reduction in fibrin formation dynamics.Results. In chronic GBF oral administration to rats at a dose of 25 mg/kg was fixed almost a 10-fold reduction in ADP-induced platelet aggregation, with increased content of these cells in the peripheral blood. Furthermore, in these conditions, there was a pronounced effect of GBF’s hypocoagulation which was implemented in inhibiting reactions inner and outer tracks of blood clotting, reducing the rate of formation of fibrin and its mechanical density.Conclusion.Thus, in experiments in vitro and in vivo for the first time revealed the ability of isoflavone 7-O-gentiobiozideformononetin extracted from the roots Maackia amurensis, inhibit the processes of vascularplatelet and coagulation hemostasis. This fact is of great practical importance, because it opens the prospective of the development of a new drug that can reduce the risk of thrombosis in various cardiovascular diseases.